ANALISIS GAP REGULASI DAN PRAKTIK DISPENSASI NIKAH DALAM HUKUM BATAS USIA PERKAWINAN DI KUA KECAMATAN TAMANSARI - Aqilah Humaira; Lathifah Hanif; Salwa Umairah; Muthmainnah Lahay; Khairunnisa (STKIP Subang, 2026)
This study examines the effectiveness of the amendment to the minimum legal age for marriage under Law Number 16 of 2019 in reducing the incidence of child marriage at the Office of Religious Affairs (KUA) of Tamansari District, Bogor Regency. It also investigates the gap between statutory provisions and their implementation in practice, as well as the role of the Marriage Guidance Program (Bimbingan Perkawinan/Bimwin) in mitigating the prevalence of child marriage. This research employed an empirical juridical method using a qualitative approach. Data were collected through semi-structured interviews with officials of the KUA of Tamansari District, field observations, and a comprehensive literature review. The findings reveal that the effectiveness of the revised legal framework remains limited due to persistent socio-economic and cultural factors, including premarital pregnancy, low educational attainment, economic hardship, and entrenched community norms. These factors contribute to a discrepancy between the legal framework and its implementation, as evidenced by the continued practice of unregistered religious marriages (nikah siri). To address these challenges, the KUA of Tamansari District implements legal mechanisms, including marriage dispensation and marriage legalization (isbat nikah), in accordance with the applicable legal provisions, while also conducting preventive public outreach and the Marriage Guidance Program. Although no specific Marriage Guidance curriculum is currently available for underage couples, community-based educational initiatives delivered through majelis taklim (Islamic study groups) have contributed to raising public awareness and were associated with a decline in the incidence of child marriage in Tamansari District during the past year.